Combining metabolomics and 16S rRNA sequencing to investigate the effects of fecal microbiota transplantation intervention in aging mice - Tianxin Zhu; Ling Yang; Zhizhong Luo; Jiqian He; Xuefeng Xu; Duosheng Luo (Journal of Holistic Integrative Pharmacy, 2024)
Aging is a complex physiological process, accompanied by metabolic and immune disorders leading to aging. The aging process yields dramatic alterations in the gut microbiota. However, there is limited evidence for a mechanistic role of the gut microbiota in aging processes. We conducted fecal microbiota transplantation from either young (4 months) or aged (22 months) donor mice into aged recipient mice (22 months) or young (4 months). Aged mice receiving young donor gut microbiota reversed aging-associated inflammation in serum and issues, and the behavioral characteristics with spontaneous activities, standing times, the number of falls, and the latency time in aged mice were alleviated. Conversely, young mice receiving aged donor gut microbiota promoted the development of inflammation, and the behavioral characteristics of aging were intensified. The relative abundance of Odoribacter, Flexispira, Veillonella, and Prevotellaceae_Prevotella were significantly enriched in aged mice, while changes were reversed in aged mice receiving young donor gut microbiota. The metabolites including indole acrylic acid, LPC (18:1/0:0), LPC (15:0/0:0), LPC (0:0/15:0) were up-regulated, and xanthine, inosine, allopurinol, N6-methyladenosine metabolites were down-regulated. After aged mice receiving young donor gut microbiota, these metabolite changes were reversed too. Analysis of the correlation between the microbiota, metabolites, and inflammatory cytokines showed indoleacrylic acid, LPC (18:1/0:0), LPC (15:0/0:0), and LPC (0:0/15:0) were negatively associated with Adlercreutzia, while positively correlated with Veillonella, Prevotellaceae_Prevotella, Streptococcus, and Odoribacter. 1-methylinosine, L-methyladenosine, allopurinol, and N6-methyladenosine were positively correlated with Desulfovibrio, and negatively correlated with Veillonella and Prevotellaceae_Prevotella. Indoleacrylic acid was negatively correlated with TGF-β. LPC (18:1/0:0), LPC (15:0/0:0), and LPC (0:0/15:0) were positively correlated with IL-10. 1-methylinosine, L-methyladenosine, N6-methyladenosine and inosine were negatively correlated with IL-6 and LPS. Our findings suggest that modulating the gut microbiome may be an appropriate treatment to promote healthy aging.